La crónica roja en TC televisión y su incidencia en el estrato socio-economico de la ciudad de riobamba periodo julio a diciembre de 2014 - Chávez Najera, Ana de las Mercedes (2016)
This paper addresses from a theoretical perspective and realistic chronicle of Tc red TV in the socio-economic strata c- Riobamba, as affects society. Participation of journalism in the crime reports, was known at different times, since it has become an essential support in the media and social communicators, allowing the strengthening of these two protagonists journalism and crime reports. Communication relates to exchange, share interiority, dialogue and is the basis of the process of transmission and reception of ideas. It is characterized by the encounter and coexistence with other disciplines, visualizing the communication object In our country every media handles blotter. On television they are transmitted through reports of violent situations that are emitted in different news. The police blotter in practice is the way it is displayed or captures information bloody events and violence that occur in the reality of our society. Feelings of insecurity that are built into the collective consciousness from such content, come to affect or influence the social imaginary. The population of the socio-economic strata C- urban Riobamba, is showing greater interest in information with the crime reports because they identify with this kind of news by the style in which its journalists transmit. TC Television newscasts in the 46 years that makes use of the blotter meet informing society with ethics and professionalism without falling into sensationalism or sensationalism, respecting the values of people.